The influence of pregnant women’s physical activity on selected perinatal parameters - Wojtyla, Anna; Mączka, Martyna (Journal of Education, Health and Sport, 2023)
AIM OF THE PAPER: Evaluation of influence of physical activity on selected perinatal parameters. MATERIALS AND METHODS: The study included 300 women in physiological pregnancy. The group was divided to physical active and non-physical active women by KAPAS survey which they fill out retrospectively. Both groups were identical in counts. Selected perinatal parameters were monitored such as: increase of body mass, in which week the pregnancy ended, necessity of using induction labor or supply with synthetic oxytocin and crotch injuries. The respondents of both groups fill up the KAPAS questionnaire second time up to 7 days after labor to assess physical activity during pregnancy. RESULTS: Both groups were homogenic in terms of somatic features. Increase of body mass was statistically significant lover in group of physically active women compare to non-active women. Birth mass of infant was significantly higher in the group of physically non-active women. It was proved that there is significant differences in physical activity during pregnancy between both groups. There were dependency between age and delivery term in physically active women. There were strong relationship between week when the pregnancy ended and necessity of using induction labor in both groups. There were no relationship between supplying with synthetic oxytocin during labor, crotch injuries and physical activity. CONCLUSION: Physical activity during pregnancy decreased the percentage of labor with inductive delivery and prevents weight gain during pregnancy. Women that were active before pregnancy sustained there physical activity during pregnancy. Women that weren’t active before pregnancy also weren’t active during pregnancy. Physical activity have no relationship with crotch injury or necessity of using synthetic oxytocin during labor.